Reinforcing social learning beyond video: lessons from the sasakawa global 2000 rice videos in kamwenge district, Uganda - Karubanga, G; Okry, F; Kibwika, P; Agea, JG; Sseguya, H (International Journal of Agricultural Research, Innovation and Technology, 2019)
The study assesses how social learning was triggered and reinforced through video-mediated extension as used by Sasakawa Global 2000 (SG 2000) from 2007 to 2010 among rice farmers in Kamwenge district, Uganda. A longitudinal study involving six focus group discussions and 100 semi-structured interviews were conducted in August 2015 to February 2016, and later 21 key informant interviews in June 2018 to generate data from farmers. While thematic-content analysis was used for the qualitative data, SPSS v.18 was used for quantitative data analysis. Results indicate that video-complementary extension methods were non-discriminative as evidenced by the diversity of farmers who participated in the demonstration sites, field days and exchange visits in terms of age mix and level of education attained. Furthermore, use of videos in extension is more effective when combined with other complementary follow-up extension methods; thus, deepening social learning among farmers. For effective scaling-up of the impact of video-mediated extension messages, use of complementary extension methods such as demonstration plots, exchange visit and field days offer greater opportunities for developing more localized videos for farmer learning. However, this requires pragmatic retooling of extension workers to effectively document local videos on the interactive learning that occurs in these complementary extension methods. Int. J. Agril. Res. Innov. & Tech. 9 (1): 66-72, June, 2019